Fundamentals of magnetic thermonuclear reactor design - Glukhikh, V. A. (Vasilii Andreevich); Filatov, Oleg Gennadievich; Kolbasov, Boris Nikolaevich (Woodhead Publishing in energy., 2018)
'Fundamentals of Magnetic Thermonuclear Reactor Design' is a comprehensive resource on fusion technology and energy systems written by renowned scientists and engineers from the Russian nuclear industry. It brings together a wealth of invaluable experience and knowledge on controlled thermonuclear fusion (CTF) facilities with magnetic plasma confinement - from the first semi-commercial tokamak T-3, to the multi-billion international experimental thermonuclear reactor ITER, now in construction in France.